Cranial nerve schwannoma – A pictorial essay - Geethapriya, Sivaramalingam; Govindaraj, Jayaraj; Raghavan, Bagyam; Ramakrishnan, Banupriya; Arafath, Rasheed; Vishwanathan, Sathyashree; Krishna, Murali (Indian Journal of Radiology and Imaging, 2020)
Schwannomas are peripheral nerve sheath tumours arising from cranial, spinal or peripheral nerves. Most of the schwannomas are benign with the rare possibility of malignant transformation. Cranial nerve schwannomas can be seen along the course of any cranial nerve in the intracranial region or head and neck location. Although a majority are solitary sporadic lesions, multiple schwannomas can be seen in syndromes like neurofibromatosis type 2 and rarely in type 1. Since intracranial schwannomas are slow-growing, clinical presentation varies between no symptoms to cranial nerve palsy. Most of the times, the symptoms are due to mass effect over the adjacent structures, foraminal widening, compression of other cranial nerves, denervation injury or hydrocephalus. Familiarity with the course of the cranial nerves, imaging appearances and clinical presentation of schwannomas helps in accurate diagnosis and possible differential diagnosis, especially in uncommon clinical and radiological appearances. In this pictorial review, we illustrate relevant anatomy of cranial nerves, imaging features of schwannomas of most of the cranial nerves, clinical presentation and differential diagnosis.
Keywords: Anatomy; clinical presentation; cranial nerve; differential diagnosis; magnetic resonance imaging; schwannoma